A Review of Resection and Surgical Ablation for Primary and Secondary Liver Cancers - White, McKenzie J.; Jensen, Eric H.; Brauer, David G. (Seminars in Interventional Radiology, 2023)
The surgical management of primary and secondary liver tumors is constantly evolving. Patient selection, particularly with regard to determining resectability, is vital to the success of programs directed toward invasive treatments of liver tumors. Particular attention should be paid toward determining whether patients are best served with surgical resection or ablative therapies. A multidisciplinary approach is necessary to provide optimal care to patients with liver malignancy.
Keywords: liver resection; liver ablation; liver-directed therapy; surgery; hepatocellular carcinoma; liver metastases